A Contested Identity: Contemporary Representation of Indonesian Chinese-Muslims on Instagram - Jesslyn Giovanni Mulyanto (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2022)
The existence of Chinese Muslims in Indonesia is surrounded by a heavily prejudiced belief that Chinese-ness and Islam are considered "unsuitable". Chinese Muslims, particularly 'converts- turned-preachers', are still considered a unique identity. However, the rise of online Islamic piety on Instagram has become one of many ways for Chinese Muslims' to represent themselves and, to some extent, "normalize" their identities. This paper discusses how Chinese-Muslim preachers, namely Felix Siauw and Koko Liem, represent their versions of Chinese-ness and Islam on Instagram, a popular visual-based social media platform in Indonesia. This research uses Multimodal Discourse Analysis (MDA) to observe the preachers' identity narratives and ways to articulate their Chinese-ness and Islam on their respective accounts posts. It is shown that the heterogeneous stances and contesting interpretations on and about Chinese-ness and Islam in the Chinese-Muslim minority group are to some extent represented through the visual appearance and narrative on Instagram of both preachers. From these two figures, the researcher concludes that elements of Islamic religious identity tend to dominate and even fade ethnic Chinese identity in the negotiations between Chinese and Muslim identities. However, their Chinese-ness was strategically used and symbolically commodified to attract the masses. These two preachers become part of the heterogeneous spectrum of Chinese-Muslim representation in Indonesia and the "pavement" for a common image of the combination of the two identities in Indonesia.